RETRACTED: Prospects for the Russian innovation industry development within the 6th technological paradigm framework - Eliseeva Ekaterina; Eliseev Yuri (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 116, 00001 (2024), https://doi.org/10.1051/bioconf/202411600001